In the cultural mirror: Influence of cultural factors on adoption of sanitation practices in rural areas: - A case of Nzaui Sub-County, Makueni County, Kenya - Eliud, Grace Kasiva; Kirimi, Lilian Mukiri; Mburugu, Kirema Nkanata; Kiogora, Domenic (African Journal of Science, Technology and Social Sciences, 2022)
Provision of adequate sanitation is among the common approaches of preventing sanitation-related diseases. However, provision of sanitation facilities may not be a sustainable sanitation solution unless the population’s behavior changes and a positive perception is embraced. This paper examined the influence of cultural factors on adoption of sanitation practices in rural areas. The article was based on field research that employed convergent research design where both qualitative and quantitative data was gathered simultaneously. Quantitative data was gathered using structured questionnaires from 100 household heads selected using stratified and proportionate simple random sampling techniques. Qualitative data was collected using an interview guide from a purposively selected focus group consisting of 9 participants. The findings were organized into themes and presented in narratives. Quantitative data was analyzed using the Statistical Package for Social Sciences (SPSS) version 25 which generated descriptive and inferential statistics to unveil the relationship between variables. From the findings, adoption of unimproved toilets was the main form of sanitation practices covering a mean of 3.3094. A unit increase in gender roles led to a 0.147 increase in adoption of sanitation practices (p-value=0.000) and a unit increase in traditions led to a 0.032 decrease in adoption of sanitation practices (p-value=0.014) in the area. Some denominations associated diarrhea with demons other than poor sanitation which was seen to facilitate poor sanitation practices. Residents believed that faeces left in the open could be used for witchcraft purposes, a tradition which had a positive impact on eradicating open defecation. Gender roles like fetching water, collecting firewood and livestock rearing in lonely places facilitated open defecation. The study recommended women inclusion in household sanitation matters and incorporation of religious leaders as advocates of sanitation behavior change. The study also recommended the need for future studies to examine adoption of sanitation practices alongside environmental, demographic and economic factors.